Functional biodiversity in soils. Development and applicability of an enzyme activity pattern measurement method - Vepsäläinen, Milja (Finnish Environment Institute, 2013)
Soil microorganisms mediate central reactions of element cycles in a heterogenic environment characterized by discontinuity of energy, nutrients, and water together with sharp pH gradients. They are diverse in species, numerous in quantity and possess a multitude of functions. One gram of soil may contain 10x109 microbial cells; for comparison, the Earth has only 7x109 human inhabitants. Species richness, evenness and composition in soils is impossible to measure, and therefore a convenient means of characterising soil microorganisms is to measure the type and rate of reactions occurring.The aim of this work was to develop a rapid, sensitive method to measure the activities of a set of soil enzymes simultaneously in a small scale. In the method, homogenized soil suspensions are investigated using fluorescent substrate analogues freeze-dried onto multiwall plates. It was shown that extraction of enzymes from soils produced inconsistent and unpredictable yields of the various activities and was therefore not applied as a pretreatment. Applicability of the method was evaluated by characterising soils treated with different agricultural practices, supporting a variety of crop plants and with fluctuating seasonal attributes. Bulk samples from experimental sites established both in agricultural and forest soils were utilized. Details of method development and of the effects of different treatments on enzyme activity pattern and on individual enzyme activities are discussed.The effects of eight crop plants, peat amendment and two consecutive sampling years yielded significant differences in soil extracellular enzyme activities. The effect of crop plants was most pronounced: eight of the measured ten activities yielded statistically significant differences in both years. The activities differed between years for six enzymes. The effect of peat was slight and was observed only two years after the addition. In another experiment, green or composted plant residues tended to enhance the activities of enzymes compared with ...